The Energy Space Density (ESD) Distribution: A New Approach to Reveal the Degree of Fracturing of the Crust in the Etna Region (Italy) - Elisabetta Giampiccolo; Tiziana Tuvè; Francesca Bianco; Edoardo Del Pezzo (The Seismic Record)
The traditional method of representing the seismicity in a region involves plotting earthquakes of various magnitudes on a map. Energy release, however, offers a different perspective for understanding seismicity, especially in volcanic areas where earthquakes are abundant and occur in the form of swarms. In this study, we analyzed earthquakes with a moment magnitude (Mw) greater than 1.5 that occurred between 2006 and 2023, which were relocated using a 3D velocity model, to examine the distribution of energy space density (ESD) in the Etna region. The ESD maps reveal the fundamental patterns of seismicity, which generally align with the local structural features. The shallow crust above 10 km plays a crucial role in energy distribution, with the highest values found in the eastern and southwestern sectors, along well-known structures bordering the unstable sector of the volcano. At deeper levels (down to 20 km), high ESD values are observed in the western sector and are related to the dynamics of magma movement at these depths. The ESD pattern improves the clarity of rock fracture density visualization, offering a more detailed view of the areas with the highest fracture density. These regions may indicate where fluid is stored beneath the volcano.